Panel conditioning and self-reported satisfaction: Evidence from international panel data and repeated cross-sections - Bert Van Landeghem (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Using data from three European countries, this paper investigates whether self-reported satisfaction data are subject to panel conditioning or a panel effect, that is, whether answers depend on whether one has previously participated in the panel. The analysis proposes a way to account for panel attrition in cases where the attrition rate is substantial, and finds international evidence for a negative panel effect. This result can be of importance e.g. in the current debate on trends in life satisfaction over time), and might stimulate further research into panel conditioning for other economic data gathered via household surveys.
Keywords: C83; I30; J10; 330; Life satisfaction; GHQ; Panel conditioning; Panel attrition; Time trends; Zufriedenheit; Panel; Datenerhebung; Deutschland; Welt